Relação do desempenho funcional e ocorrência de quedas em idosos - NUNES, Leonardo Geamonond (2018)
The present study aimed to identify the prevalence of falls and its relationship with sociodemographic aspects, health indicators and low physical performance in the elderly. This study was characterized as observational, of the analytical type with a cross-sectional design, with a sample of 457 elderly, of both sexes, living in the urban area of the city of Alcobaça, State of Bahia. Data were collected through an individual interview, with sociodemographic information, health indicators, functional performance evaluation, presence and absence of falls in the last 12 months. The functional limitation was evaluated by the "Short Physical Performance Battery" (SPPB) and the occurrence of falls was self-reported. Data analysis was performed using descriptive and inferential statistics (binary regression) p≤0.05. The prevalence of falls in the studied population was 28.7% (n = 131), and this condition was more prevalent among women, those who reported two or more diseases and had a performance in the walk test at or above the 25th percentile. The results of this study may support health promotion programs aimed at reducing the occurrence of falls among the elderly.